Gawai pada Anak Usia Dini: Peran Ibu dalam Pendampingan Anak Era Disrupsi 4.0 - Widyandari, Devi; Asnatasia Maharani, Ega (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
Technological advances that are growing rapidly, require parents, especially mothers, to be technology literate. Gadgets are now a primary need, especially the condition of School from Home, everything has to be online. The purpose of this study to analyze the role of parents, especially mothers, in the use of gadgets in children in the province of DIY. The research method used is descriptive quantitative research with a survey. The data were analyzed statistically using percentages and presented descriptively to reveal the mothers' role in the use of gadgets by children. The results showed that in the Special Region of Yogyakarta, the mothers' role in the use of gadgets by children was in the medium category, reaching 44.8%. The roles, based on the parenting aspect, were divided into two: control and warmth. In the former dimension, 41.2% was in the medium category, and 24.8% was in the low category. Meanwhile, in the latter, 34% was medium, and 31% was high. The roles, especially those in the medium category, were influenced by several factors, such as education, parents' perceptions of using gadgets during the School from the Home period, and the children's entertainment media. The findings of this study have implications for parents, especially mothers, to increase assistance in the use of gadgets for children.